2015
DOI: 10.1111/jdi.12400
|View full text |Cite
|
Sign up to set email alerts
|

Postabsorptive hyperglucagonemia in patients with type 2 diabetes mellitus analyzed with a novel enzyme‐linked immunosorbent assay

Abstract: Aims/introductionThe aims of the present study were to investigate the performance of a novel sandwich enzyme‐linked immunosorbent assay (ELISA) for measuring glucagon (1–29) with monoclonal antibodies against both the C‐ and N‐terminal regions of glucagon (1–29), and to analyze the differences in plasma levels and responses of glucagon (1–29) to oral glucose loading in normal glucose tolerance (NGT) subjects and patients with type 2 diabetes mellitus.Materials and MethodsThe cross‐reactivity against proglucag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
41
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(47 citation statements)
references
References 38 publications
6
41
0
Order By: Relevance
“…The analyzed clinical characteristics of the participants are presented in Table, indicating a group comprising young adults with relatively well‐controlled diabetes, but with exhausted endogenous insulin production. The plasma glucagon level was 28.1 ± 17.7 pg/mL, which was comparable with that obtained in a previous report of Japanese patients with type 2 diabetes. However, the values were widely spread (5.7–95.2 pg/mL), and did not correlate with plasma glucose levels (33–401 mg/dL; Figure a).…”
Section: Resultssupporting
confidence: 88%
“…The analyzed clinical characteristics of the participants are presented in Table, indicating a group comprising young adults with relatively well‐controlled diabetes, but with exhausted endogenous insulin production. The plasma glucagon level was 28.1 ± 17.7 pg/mL, which was comparable with that obtained in a previous report of Japanese patients with type 2 diabetes. However, the values were widely spread (5.7–95.2 pg/mL), and did not correlate with plasma glucose levels (33–401 mg/dL; Figure a).…”
Section: Resultssupporting
confidence: 88%
“…In this study, as in the previous report [5][6][7][8][9], it was found that the average of fasting glucagon and FPG became higher with worsening of glucose tolerance, but there was no significant difference in fasting insulin and CPR level among NGT, preDM and DM group. Significant correlation was found between fasting glucagon level and the indicators of insulin sensitivity such as HOMA-IR and Matsuda index.…”
Section: Elevated Fasting Glucagon In Subjects With Impaired Glucose supporting
confidence: 82%
“…It is reported that fasting glucagon level is higher in T2DM compared to subjects with normal glucose tolerance (NGT) [3,4]. Inappropriate glucagon increase in the early phase of oral glucose tolerance test, and delayed glucagon suppression has been observed in diabetes patients [5][6][7][8][9], compared to immediate suppression of glucagon after glucose ingestion in the subjects with normal glucose tolerance. In normal physiology, a variety of factors have been known to influence glucagon regulation, such as insulin [10][11][12], GLP-1 [13][14][15][16][17][18][19], amino acids [20][21][22][23][24], autonomic nervous system [25][26][27], free fatty acids [28], and Zn 2+ ion [29].…”
mentioning
confidence: 99%
“…In contrast to the complete lack of endogenous insulin, as assessed on the basis of a plasma C-peptide level below the detection limit, pancreatic glucagon was detectable, albeit at very low levels, in four out of seven patients with a total pancreatectomy. Cross-reactivity of glucagon-related peptides, such as oxyntomodulin and glicentin, in the glucagon assay has long been under debate, but sandwich enzyme-linked immunosorbent assays using a combination of C-and N-terminal antiglucagon antibodies, as used in the present study, have been reported to detect pancreatic glucagon with very small crossreactivity with other glucagon-related peptides 14,15 . Previous studies have suggested that pancreatic glucagon is synthesized and secreted from the gut [16][17][18] at levels detectable even in patients with total pancreatectomy 18 , and that such gut-derived glucagon is secreted in response to glucose intake and significantly affects glucose homeostasis 18 .…”
Section: Discussionmentioning
confidence: 90%